Computer Vision for Identifying and Classifying Green Coffee Beans: A Review - Ligar, Bonang Waspadadi (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2022)
Coffee is widely consumed around the world, also considered one of the most important beverages today.  Factors contributing to the quality of coffee beans such as color, texture, size, aroma, etc. and other processes along the production chain such as plant, roasting, and grinding. Those processes will be worthless if the quality of the coffee bean is low. It is important to only use the best quality coffee beans. Therefore, the challenge is to develop a system that uses computer vision to either identify high quality beans or classify them by their species to ease the effort needed by all actors in the supply chain. Providing information for end customers is a defining factor to push forward the coffee industry. This paper aims to review literatures within the topic of using computer vision for coffee beans. After reviewing a selected number of studies which corresponds with the topic chosen in our paper, computer vision techniques were used for two main reasons, identification and classification. Researches on this topic are still limited. Hence, it can be concluded that there are still plenty of room for study on this topic. This study also aims to help provide research material for future researchers.